Applying ultra-wide band radio technology to computer-assisted medical applications - Loh, Yuin Hay. (2009)
Monitoring health parameters of a patient is an important aspect in the biomedical field. Non-invasive vital sign monitoring benefits the work of detecting life during disaster, the monitoring of patient with burnt skin and the convenience in out of hospital monitoring of patients‟ health parameters. Ultra-Wideband radio technology has the ability to determine the "time of flight" of the direct path of the radio transmission between the transmitter and receiver at a higher precision as compared to the conventional radio technology, due to the short pulse duration. These pulses being very short in time space (less than 60 cm for a 500 MHz wide pulse, less than 23 cm for a 1.3 GHz bandwidth pulse), which means most signal reflections do not overlap the original pulse, and thus the traditional multipath fading of narrow band signals does not exist. This makes it worthy to study any possible applications exploiting its multipath resistance and high accuracy property. In this project, Ultra-Wideband radio technology equipments available in the laboratory are being used to acquire breathing rate of the human under test. The collected data is then compared with commercial chest band, which is non-radio frequency type equipment for acquiring breathing rate. A study on Ultra-wideband radio technology for the possibility of penetrating the human body is conducted. This study is done progressively in stages by both experiments and signal processing to verify any possibility of using the direct path signal, if any, for position tracking.